2015
DOI: 10.17795/whb-25342
|View full text |Cite
|
Sign up to set email alerts
|

Health Knowledge and Health Promoting Lifestyle Among Women of Childbearing age in Shiraz

Abstract: Background: Health promotion is receiving an ever increasing attention regarding its prominent role in health of population. Health promoting lifestyle could be due, in some part, to enhancing knowledge about healthy behaviors. Objectives: Due to the importance of healthy lifestyle in current situation of chronic diseases in Iranian society, the aim of this study was to determine the correlates of health promoting life style with a special emphasis on the role of health knowledge among women of reproductive ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…The scoring of the HPLP2 questionnaire is based on a 4-point scale; each score is as follows: never: 1, sometimes: 2, often: 3, normally: 4; adding up to a highest score of 208 and lowest score of52.Lin et al, showed that Cronbach's α for this questionnaire was 0.96 and that for each subscale ranged from .77 to .87. Also, its reliability and validity on Iranian women has been published previously (21). Menopause severity was assessed by the Menopause Rating Scale (MRS) questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…The scoring of the HPLP2 questionnaire is based on a 4-point scale; each score is as follows: never: 1, sometimes: 2, often: 3, normally: 4; adding up to a highest score of 208 and lowest score of52.Lin et al, showed that Cronbach's α for this questionnaire was 0.96 and that for each subscale ranged from .77 to .87. Also, its reliability and validity on Iranian women has been published previously (21). Menopause severity was assessed by the Menopause Rating Scale (MRS) questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…cluded studies except of one study (Ahmadipour & Kiarash, 2016), a significant relationship has been reported between education and healthy lifestyle. For determinant of spouse's education, there was a significant relationship in three studies (Abedi et al, 2015;Ahmadi et al, 2015;Mirghafourvand et al, 2014). There was a significant relationship between spouse's job and healthy lifestyle in two studies (Abedi et al, 2015;Amirabadizadeh et al, 2016).…”
Section: Description Of Studiesmentioning
confidence: 96%
“…In all studies, health-promoting behaviours and their related factors were analysed. In most studies (Abedi et al, 2015;Ahmadi et al, 2015;Ahmadipour & Kiarash, 2016;Amirabadizadeh et al, 2016;Anbari et al, 2015;Bakouei et al, 2017;Enjezab et al, 2012;Mirghafourvand et al, 2014;Tol et al, 2018), Walker's health-promoting lifestyle Profile (HPLP 2) (Walker et al, 1987) was used to investigate health-promoting behaviours. Two studies used a researcher-made questionnaire (Mahdipour et al, 2013;Rafiee et al, 2014), and one study applied the Lifestyle Questionnaire (LSQ) designed by La'li et al in Iran (Zare & Khaluee, 2016).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…A number of studies have found a positive relationship between health literacy and health-promoting behaviors [13-15]. For example, studies have found a significant association between health knowledge and health-promoting lifestyles among women of childbearing age [16]. In addition, eHealth literacy is actively promoted via health education.…”
Section: Introductionmentioning
confidence: 99%